THE IMPORTANCE OF USING EPIDURAL FAT IN THE PREVENTION OF OPERATED SPINE SYNDROME - KH.D. RAKHMONOV; R.N. BERDIEV; F.G. KHOZHANAZAROV (Avicenna Tajik State Medical University, 2019)
Objective: Improving the results of microsurgical treatment of recurrences of a herniated inter-vertebral disc (HIVD) in operated spine syndrome. Methods: The results of surgical treatment of 70 patients with lumboishialgia and disco-radicular conflict due to the HIVD were studied. Among the total number of sick women were 26 (37.1%), men - 44 (62.9%). A comprehensive examination of patients included X-ray, tomography and/or MRI of the lumbosacral section of the spinal column, as well as the electromyography study of lower limbs. Dynamic examination of patients was carried out before and after surgery, and the time frame through 3, 6 and 12 months after surgery. Results: In the studying the levels of lesions of the spine divisions, it was found that the most common HIVD was observed at the level of L5 -S1 - in 36 (51.4%); L4 -L5 HIVD was found at 29 (41.4%); and L3 -L4 - at 5 (7.1%) cases. In 40 (57.1%) patients out of 70 had microsurgical discectomy in the traditional way and in 30 (42.9%) cases performed a microsurgical discectomy with the laying of free fat in the interstitial space. The results of the comparative analysis showed that patients in both groups had a decrease in the intensity of pain syndrome compared to the condition before operation. At the same time, in the patients of the main group, this parameter was better though the 6 and 12 months than in the control group (p<0.01). Conclusion: Proposed microsurgical discectomy with the laying of free fat in the interstitial space during re-operation on the recurrence of HIVD, along with its simplicity in performance has shown great efficiency without requiring additional costs. A decrease in the number of unsatisfactory outcomes by 2-3 times was noted with a simultaneous increase in the number of satisfactory and good results of surgical treatment of this disease.